2000
DOI: 10.1055/s-2000-5887
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic properties of long-acting insulin analogue NN304 in comparison to NPH insulin in humans

Abstract: NN304 is a long-acting insulin analogue that is acylated with a 14-C-fatty acid chain. Protraction of action of this novel insulin analogue is due not to slow absorption after subcutaneous administration but to reversible binding to albumin. We investigated the pharmacokinetic and pharmacodynamic properties of insulin analogue NN304 (0.3 and 0.6 U/kg) in comparison to NPH insulin (0.3 and 0.6 IU/kg) in 10 healthy volunteers performing a randomised, double-blind, cross-over, placebo-controlled glucose clamp stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 13 publications
3
52
0
2
Order By: Relevance
“…These insulin analogs make use of different principles for achieving a protracted insulin profile, such as changing the isoelectric point (insulin glargine) or acylation of the insulin molecule (insulin detemir). Previous studies have confirmed both a delayed and a sustained blood glucoselowering effect with insulin detemir compared with NPH insulin in healthy subjects (10,11). However, the results show that a higher molar dose of insulin detemir is needed to achieve comparable glycemic control similar to that observed with NPH insulin (10).…”
mentioning
confidence: 50%
“…These insulin analogs make use of different principles for achieving a protracted insulin profile, such as changing the isoelectric point (insulin glargine) or acylation of the insulin molecule (insulin detemir). Previous studies have confirmed both a delayed and a sustained blood glucoselowering effect with insulin detemir compared with NPH insulin in healthy subjects (10,11). However, the results show that a higher molar dose of insulin detemir is needed to achieve comparable glycemic control similar to that observed with NPH insulin (10).…”
mentioning
confidence: 50%
“…Thus an insulin analogue bound to one or more plasma proteins has greater access to hepatocytes than to peripheral target tissues. Insulin detemir (NN304) (B29Lys(ε-tetradecanoyl),desB30 human insulin) is a soluble insulin analogue with a C 14 fatty acid side-chain at position B29 [4]. In the monomeric state, this side-chain binds to the fatty acid binding sites of albumin in plasma, developing equilibrium between free and albumin bound analogue [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in vivo pharmacodynamic (and clinical) studies have shown that insulin detemir does have a reduced molar potencyFabout 25% that of human insulin. 44,45 This is probably due to a relatively reduced rate of access from the plasma compartment to the interstitial fluid with an increased rate of nonreceptor-mediated clearance. 46 Consequently, insulin detemir is marketed in a formulation that is four times the molar strength of human insulin so as to maintain parity in unit doses and injection volumes.…”
Section: Insulin Detemir At the Level Of The Receptormentioning
confidence: 99%